Increase in the Indian Economy Due to the Indian IT Sector - Bhattacharyya, Raunak (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Currently a worldwide powerhouse, India’s Information Technology (IT) sector has had a significant positive influence on the country’s economic development. In terms of GDP, employment, and foreign currency profits, the sector has significantly boosted the economy. Nearly all economic sectors have seen increases in productivity and competence thanks to the IT industry. It has made a significant contribution to establishing the nation as a favored investment destination for international investors and producing a significant amount of employment possibilities in India as well as the USA, Europe, and other regions of the globe. Since it has shown its ability to provide both on-shore and off-shore services to customers worldwide, India is the top offshoring location for IT businesses worldwide. The Information Technology/Information Technology Enabled Services (IT/ITeS) sector in India, which has a dominant position internationally, has been gradually boosting exports and generating job opportunities. The Indian middle class has gained a significant position and its level of life has significantly improved thanks to the IT industry. In comparison to other economies, India’s IT sector has grown remarkably. The Indian economy has grown as a result of the industry’s advancements in revenue growth during the last two decades. In this essay, we have examined the many contributions that India’s IT sector has made to its development.